2021
DOI: 10.1093/tas/txab028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-protein distillers dried grains on growth performance of nursery pigs

Abstract: A total of 300 pigs (DNA 400 × 200, Columbus, NE), initially 11.1 kg, were used in a study to evaluate the effects of increasing amounts of high-protein distillers dried grains (HP DDG) on growth performance and to estimate its energy value relative to corn. Pigs were weaned, placed in pens with 5 pigs each, and fed a common diet for 21 d after weaning. Then, pens were assigned to treatments in a randomized complete block design. There were 5 treatments with 12 replicates per treatment. Treatments consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Similarly, these equations have been obtained with complete feeds that often contain higher levels of ash than single ingredients and the mean chemical, and physical characteristics of fibre in the database values may differ markedly from those of a given ingredient. Therefore, equations obtained on complete feeds, especially those including an intercept (as above) should never be applied to single ingredients ( Cemin et al, 2021 ). More generic equations based on the average DE or ME contributions of each energy-yielding nutrient may then be applied to both complete feeds and ingredients; the energy contribution of ash is then considered as nil and/or the negative effect of ash on dietary DE or ME values is considered for all nutrients.…”
Section: Prediction Of De and Me Values Of Complete Feeds For Pigs And Poultrymentioning
confidence: 99%
“…Similarly, these equations have been obtained with complete feeds that often contain higher levels of ash than single ingredients and the mean chemical, and physical characteristics of fibre in the database values may differ markedly from those of a given ingredient. Therefore, equations obtained on complete feeds, especially those including an intercept (as above) should never be applied to single ingredients ( Cemin et al, 2021 ). More generic equations based on the average DE or ME contributions of each energy-yielding nutrient may then be applied to both complete feeds and ingredients; the energy contribution of ash is then considered as nil and/or the negative effect of ash on dietary DE or ME values is considered for all nutrients.…”
Section: Prediction Of De and Me Values Of Complete Feeds For Pigs And Poultrymentioning
confidence: 99%
“…Similar to this work, at high Leu:Lys ratios, growth performance of weaned pigs was reduced. The effect of high Leu:Lys ratio when main protein sources are replaced with GDDY or other corn-fermented protein products ( Yang et al 2018a , Cemin et al 2021 ) has been well documented in growing-finishing pigs ( Rojo 2011 , Cemin et al 2019 , Clizer 2021 , Kwon et al 2022 ). It is suggested that in growing finishing pigs Leu:Lys ratios above 150% are expected to negatively impact performance ( Htoo et al 2014 , Cemin et al 2019 , Kwon et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Excess Leu generates an antagonistic effect between BCAA because they share the same enzyme complex (BCAAs aminotransferase and BCAA a-ketoacid dehydrogenase complex) as the first step in their degradative pathway ( Langer et al 2000 , Sanderson and Naik 2000 , Wiltafsky et al 2010 ). Therefore, increasing the ratio of Ile and Val to Lys as the Leu:Lys ratio increases can be used to avoid detrimental impacts on growth performance ( Htoo et al 2007 , Cemin et al 2021 ). Acosta et al (2021) suggested including up to 10% of corn-fermented protein products in diets for weaned pigs during phase 1 and 2 to reduce the negative effects on growth performance caused by the high concentration of Leu, which may negatively impact metabolism of Val and Ile.…”
Section: Discussionmentioning
confidence: 99%
“…New technology in the ethanol industry allows dry-corn milling biorefineries to fractionate corn fiber from fermentable corn constituent’s prefermentation resulting in greater ethanol yields for the facility ( Sekhon et al, 2015 ). Due to the earlier fractionation of corn fiber in this process, the subsequently produced dried distillers grains (DDG) are more concentrated and have a higher crude protein content that fits specific parameters for use as a feed in nursery, growing, and finishing diets of pigs as a potential cost-effective replacement for soybean meal ( Cemin et al, 2021 ; Rao et al, 2021 ). High-protein DDG have also been evaluated as a suitable feed in beef cattle feedlot diets ( Garland et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%